Contributions of a Professional Development Course to Language Teacher Identity Development: Critical Incidents in Focus. (September 2022) - Nazari, Mostafa; De Costa, Peter I.
Despite the widely recognized significance of critical incidents (CIs) in teachers' professional learning, little research has investigated the role of CIs in language teacher identity development. This study attempts to fill this gap by exploring the contributions of a Telegram-based professional development course—framed around CI storying—to the language teacher identity development process of a group of teachers. Data were collected from 10 teachers before, during, and after the course. Data analyses indicated that, before the course, CIs negatively influenced the teachers' agency and emotions. Participation in the course contributed, however, to the teachers' enhanced agency and greater emotion regulation. In addition, the course afforded the teachers an opportunity to experience further professional socialization and collegial engagement. Our findings revealed that during the course, the teachers developed greater expertise in storying their CIs and discussed higher order issues relevant to the multiplicity of identity as connected to sociocultural-educational dimensions. These findings suggest that emotions and agency are two significant identity aspects that are profoundly influenced by and influence CIs. Our article closes with a discussion of the implications of embedding CIs in professional development courses to help teachers (re)construct their identities.